Study on spiral source models revealing groundwater transfusion effects on pile foundation ground heat exchangers. (May 2015) - Zhang, Wenke; Yang, Hongxing; Cui, Ping; Lu, Lin; Diao, Nairen; Fang, Zhaohong
Abstract: This paper presents a new spiral source heat transfer model for simulating the heat transfer performance of pile foundation ground heat exchangers (GHEs) with existence of groundwater transfusion. The model takes heat conduction and convection of groundwater into account and is more accurate than those previously proposed such as solid cylindrical model and ring-coil model to describe the heat transfer behavior. Besides, some shortages and deficiencies are improved and overcome, especially in terms of the configuration of spiral heat transfer tubes. The analytical solutions of the model are obtained to exhibit the temperature response at any point in the underground medium around the pile foundation GHEs. The parameters that exert impacts on the heat transfer process has been investigated and discussed in the paper. The pure conduction case and combined heat transfer case are compared, and the heat exchange efficiency between the pile foundation GHEs and surrounding medium can be improved as a result of the influence of groundwater transfusion. The meliorative effect is becoming increasingly evident with time or velocity of groundwater. The research contributes to more understanding of the potential for pile foundation GHEs and the degrees which the heat transfer efficiency affected by groundwater flow.